2005
DOI: 10.1159/000087637
|View full text |Cite
|
Sign up to set email alerts
|

Is <i>Lactobacillus rhamnosus</i> GG Effective in Preventing the Onset of Antibiotic-Associated Diarrhoea: A Systematic Review

Abstract: Objective: To evaluate the efficacy of Lactobacillus rhamnosus GG in the prevention of antibiotic-associated diarrhoea. Data Sources: A computer-based search of MEDLINE, CINAHL, AMED, the Cochrane Controlled Trials Register and the Cochrane Database of Systematic Reviews was conducted. A hand-search of the bibliographies of relevant papers and previous meta-analyses was undertaken. Review Methods: Trials were included in the review if they compared the effects of L. rhamnosus GG and placebo and listed diarrhoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 41 publications
(33 reference statements)
0
42
0
3
Order By: Relevance
“…[45][46][47][48] Treatment with a probiotic was started when antibiotic therapy was initiated for treatment of an acute respiratory infection (otitis media) in most of these studies. Treatment with probiotics compared with placebo reduced the risk of developing antibiotic-associated diarrhea from 28.5% to 11.9% (relative risk [RR]: 0.44 [95% CI: 0.25-77]; P ϭ .006).…”
Section: Prevention Of Antibiotic-associated Diarrheamentioning
confidence: 99%
“…[45][46][47][48] Treatment with a probiotic was started when antibiotic therapy was initiated for treatment of an acute respiratory infection (otitis media) in most of these studies. Treatment with probiotics compared with placebo reduced the risk of developing antibiotic-associated diarrhea from 28.5% to 11.9% (relative risk [RR]: 0.44 [95% CI: 0.25-77]; P ϭ .006).…”
Section: Prevention Of Antibiotic-associated Diarrheamentioning
confidence: 99%
“…Lactobacillus GG, Saccharomyces boulardii ) significantly reduce the risk of diarrhea in children treated with antibiotics [8, 9]. Other meta-analyses have shown that probiotics are modestly effective also in the general population [10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the studies differ in design, sample population, types of antibiotics studied and formulation of bacterial enriched drinks, end points and definition of diarrhoea. Therefore, it is difficult to assess the efficacy of probiotics on AAD (Hawrelak et al, 2005).…”
Section: Introductionmentioning
confidence: 99%